Geological structure and paleogeographic zoning of the Khadum formation in Pre-Caucasus - E. A. Krasnova; A. V. Stoupakova; A. N. Stafeev; N. P. Fadeeva; N. Sh. Yandarbiev; A. A. Suslova; R. S. Sautkin; M. E. Voronin; P. B. Stepanov; A. A. Knipper; Ya. A. Shitova (Georesursy)
Unconventional oil and gas resource development and exploration is the one of the most prospective concept in petroleum geology. High carbon Khadum facies are investigated as unconventional resources in the Precaucas basin and contain gas, gas condensate and oil accumulations. Oligocene and Lower Miocene structure, prospectivity and fields distribution are the one of the most relevant subjects nowadays.This study is focused on the main stages Late Eocene and Early Oligocene deposits formation and the paleogeography of the Khadum formation in the Precaucas oil and gas basin. The new prospective zones are developed in Khadum formation based on the complex analysis of seismic, paleogeography and lithofacies analysis.